2021
DOI: 10.1371/journal.ppat.1009849
|View full text |Cite
|
Sign up to set email alerts
|

Acute SARS-CoV-2 infections harbor limited within-host diversity and transmit via tight transmission bottlenecks

Abstract: The emergence of divergent SARS-CoV-2 lineages has raised concern that novel variants eliciting immune escape or the ability to displace circulating lineages could emerge within individual hosts. Though growing evidence suggests that novel variants arise during prolonged infections, most infections are acute. Understanding how efficiently variants emerge and transmit among acutely-infected hosts is therefore critical for predicting the pace of long-term SARS-CoV-2 evolution. To characterize how within-host div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
112
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(142 citation statements)
references
References 58 publications
(131 reference statements)
30
112
0
Order By: Relevance
“…Our results demonstrate that epidemiologically-linked individuals in a superspreading event share little to no intrahost viral diversity even at sites where mutations fix during the event, corroborating studies reporting narrow transmission bottlenecks in other settings [3,4,[6][7][8].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results demonstrate that epidemiologically-linked individuals in a superspreading event share little to no intrahost viral diversity even at sites where mutations fix during the event, corroborating studies reporting narrow transmission bottlenecks in other settings [3,4,[6][7][8].…”
Section: Introductionsupporting
confidence: 87%
“…So far, efforts to understand how transmission shapes the evolution of SARS-CoV-2 have mainly focused on small household events or nosocomial pairs [3][4][5][6][7]. Such studies point to a narrow transmission bottleneck that significantly reduces viral genetic diversity at the start of each infection [3,4,[6][7][8]. While exact estimates of the bottleneck range from 1 to 15 virions, it is clear that a limited number of virions initiate most human infections.…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Good concordance was achieved in replicated sequencing for samples with relatively high viral loads (Ct ≤30), while a high proportion of discordant iSNVs was observed in samples with relatively lower viral loads (Ct >30), possibly generated by PCR biases 16 , 17 (Supplementary Fig. 2c–h ).…”
Section: Resultsmentioning
confidence: 95%
“…Longitudinal sequencing of some cases of chronic infection has uncovered striking mutational patterns of evolution, and revealed that the rate of evolution is much higher than that observed along transmission chains of acutely infected individuals (e.g., [6][7][8] ). Indeed, several recent reports have found that the intra-host variation during acute infections is quite limited [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%